2021
DOI: 10.1108/ijchm-12-2020-1467
|View full text |Cite
|
Sign up to set email alerts
|

Making memories: a consumer-based model of authenticity applied to living history sites

Abstract: Purpose Underpinned by the consumer-based model of authenticity (CBA), this study aims to investigate whether leisure involvement, object-based and existential authenticity, host sincerity and engagement stimulate positive memorable visitor experiences in a distinctive commercial hospitality setting: a living history site. Design/methodology/approach Quantitative data were gathered from living history site visitors (n = 1,004), with partial least squares structural equation modeling used to test the hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 69 publications
(122 reference statements)
0
21
0
Order By: Relevance
“…Authenticity is central to the heritage tourism experience (Hargrove, 2002 ; Zatori et al, 2018 ) verified the relationship among participation, authenticity, and the tourist experience and found that authenticity correlates with the tourism experience. Kesgin et al ( 2021 ) confirmed that OBA positively affects MTEs at historical sites, whereas Pine et al ( 1999 ) suggested that people immersed in tourism activities are more likely to have unforgettable experiences. EA comes from engaging in tourism activities (Wang and Mattila, 2015 ); thus, tourists' participation in activities can create unforgettable experiences (Kim, 2014 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Authenticity is central to the heritage tourism experience (Hargrove, 2002 ; Zatori et al, 2018 ) verified the relationship among participation, authenticity, and the tourist experience and found that authenticity correlates with the tourism experience. Kesgin et al ( 2021 ) confirmed that OBA positively affects MTEs at historical sites, whereas Pine et al ( 1999 ) suggested that people immersed in tourism activities are more likely to have unforgettable experiences. EA comes from engaging in tourism activities (Wang and Mattila, 2015 ); thus, tourists' participation in activities can create unforgettable experiences (Kim, 2014 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Memorable tourism experiences (MTEs), which are experiences that tourists actively remember after visiting a tourist destination (Kim et al, 2012 ), are cognitive evaluations of external stimuli (such as tourism authenticity). Relevant studies have shown that tourism authenticity correlates with MTEs (Kesgin et al, 2021 ). Moreover, cognitive evaluations of external stimuli produce emotional responses.…”
Section: Introductionmentioning
confidence: 99%
“…To build up a authentic experiential space, it needs to follow up with service innovation and further maintenance and innovation over the entire life cycle. This could involve co-creation, engaging with local community and visitors (Guan et al , 2021; Hao, 2020; Kesgin et al , 2021; Liu et al , 2022). Innovation process studies suggested that neglecting implementation phases can create a black hole in process theory and render an explanatory framework of innovation antecedents incomplete (Perry-Smith and Mannucci, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are many valuable traditions with potential for creating an authentic experience for visitors (Benur and Bramwell, 2015;Yi et al , 2017), for examples, historic buildings and attractions, arts and crafts, traditional farming and other related activities, and folklore handed down from generation to generation. This can enhance the customer experience, increasing attractiveness and building a strong differentiation advantage in the market ( Kuo et al , ;Kesgin 2018Kesgin et al ., 2021. More importantly, innovation utilising traditions and heritage can, simultaneously, achieve sustainable objectives, encompassing heritage conservation, community development, and tourism economy (Menicucci, 2018;Widjojo and Gunawan, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Reconceptualizing tour-guiding accordingly, guides serve to balance tourists' demands for authentic experiences with ever-evolving sharing economy trends. Guides can transform sites into tourist attractions or authentic experiences (Kesgin et al 2021), but professionalism and standardization issues create ambiguity around their role (Ap and Wong 2001). The curatorial role of tour guides in interpreting heritage, for example, can influence tourists' perceptions of destination authenticity (Io and Hallo 2011).…”
Section: Introductionmentioning
confidence: 99%